Estudio socio-económico y financiero de los pequeños productores de maíz dulce de la zona agrícola del cantón Balzar provincia del Guayas, año 2011 - Bravo Loor, Ana Lucia (2012)
The present investigation was carried out with the purpose of improving the quality of the small farmers' of sweet corn of the canton life Balzar, by means of the financing of a watering system for leak that allows them to increase its production and productivity in the cultivation. The gathering of data was made by means of the application of surveys to the farmers, conformed by twenty-four questions the same ones that were distributed in four topics to study like they are the socioeconomic, productive, financial and commercial part, besides technical of observation and it photographs. In the obtained results it was demonstrated that the farmers are developed in an economy of subsistence when being proven that 90% of the family is composed by a high number of members that added to the first floor production level, to the payment of rates of it interests bigger to 30% and the intermediation to the moment to market their products, they impede that these they have a socio-economic growth. The lack of support of the government and not government entities puts in manifesto the difficult socio-economic and financial situation for which the small farmers cross, because they don't have technical attendance, financing at low costs to carry out their cultivations as well as a watering system that allows them to carry out labored activity in summer time and to have the freedom of choosing a direct channel of commercialization for their product when selling They were designed and they applied the techniques and appropriate methods that once analyzed they contributed to the confirmation of the hypothesis it stops later on to emit the respective conclusions and recommendations based on the developed study. The propoused targets of this research were reachead testing the investment project to purchase irrigation equipment, the research gave a VAN of $3.967,00 end TIR of 46%, these viability of this project.